KAJIAN TERHADAP MODEL TRAUMA HEALING PENDETA TERHADAP ANAK KELUARGA KORBAN PEMBUNUHAN TERORIS DI DESA KALEMAGO, POSO - Yuyun Agnes Kiding Allo; Orin Devisa (Institut Injil Indonesia, 2023)
The author raised this title starting from the problem where there children who are families of victims of terrorist killings in Kalemago Village, Poso who are traumatized must be helped in the right way. In this case, the Pastor carries out her role as a counselor to help these children so they can recover from the trauma experienced by carrying out the trauma healing process. This research wants to find out how the results of the trauma healingmodel used by the Pastor in Kalemago Village in carrying out therapy for children in the village are. This research is a descriptive qualitative research. Research data is data collected by the author through the interview stage as well as through the observation stage conducted by the author as the research location. The research data was obtained by interview method which then went through the process of reduction, presentation and drawing conclusions. He results of this study indicate that the trauma healing model used is play therapy where this model is appropriate but the results are not optimal because the trauma recovery process takes a long time and is gradual, while the pastor only does this therapy three times in a period of two months.